Circulating blood cells and extracellular vesicles in acute cardioprotection - Davidson, Sean M (Cardiovasc Res, 2019)
During an ST-elevation myocardial infarction (STEMI), the myocardium undergoes a prolonged period of ischaemia. Reperfusion therapy is essential to minimize cardiac injury but can paradoxically cause further damage. Experimental procedures to limit ischaemia and reperfusion (IR) injury have tended to focus on the cardiomyocytes since they are crucial for cardiac function. However, there is increasing evidence that non-cardiomyocyte resident cells in the heart (as discussed in a separate review in this Spotlight series) as well as circulating cells and factors play important roles in this pathology. For example, erythrocytes, in addition to their main oxygen-ferrying role, can protect the heart from IR injury via the export of nitric oxide bioactivity. Platelets are well-known to be involved in haemostasis and thrombosis, but beyond these roles, they secrete numerous factors including sphingosine-1 phosphate (S1P), platelet activating factor, and cytokines that can all strongly influence the development of IR injury. This is particularly relevant given that most STEMI patients receive at least one type of platelet inhibitor. Moreover, there are large numbers of circulating vesicles in the blood, including microvesicles and exosomes, which can exert both beneficial and detrimental effects on IR injury. Some of these effects are mediated by the transfer of microRNA (miRNA) to the heart. Synthetic miRNA molecules may offer an alternative approach to limiting the response to IR injury. We discuss these and other circulating factors, focussing on potential therapeutic targets relevant to IR injury. Given the prevalence of comorbidities such as diabetes in the target patient population, their influence will also be discussed. This article is part of a Cardiovascular Research Spotlight Issue entitled ‘Cardioprotection Beyond the Cardiomyocyte’, and emerged as part of the discussions of the European Union (EU)-CARDIOPROTECTION Cooperation in Science and Technology (COST) Action, CA16225.